Institutional repositories - Swan, Alma (Henry Stewart Talks, 2012)
Open access, Research literature, Journal articles, Open data, Citation impact, Research impact, Research visibility, EPrints, DSpace, University profile, Author profile, Digital repositories, Business planning for repositories, Open licensing, SMEs